Economically viable Mushroom (Pleurotus djamor) farming for nutritional security in Uttarakhand - NAYAK, HARAPRIYA; KUSHWAHA, ARCHANA; SRIVASTAVA, SARITA; KUSHWAHA, K P S; CHANDRA BEHERA, PRAKASH; BALA, PRAKASH; SHAHI, N C; KUMAR, ANIL (The Indian Journal of Agricultural Sciences, 2022)
Pink oyster mushroom (Pleurotus djamor) owns a pleasant colour, good sensory attributes, high nutritional value, anti-oxidant, anti-microbial and medicinal properties. Cultivation of different types of mushroom has been accepted as a short-term income generating avenue under crop production for livelihood of the farmers. The present study was carried out to assess the nutritional quality, anti-oxidant activities and economic benefits of pink oyster mushroom at Research farm of G B Pant University of Agriculture and Technology, Pantnagar, Uttarakhand during 2015–18. The fresh whole mushroom was assessed for yield and physical parameters. It was exposed to 60±20C temperature for 8 h to prepare dried mushroom powder. The dried powder was used for proximate composition analysis and anti-oxidant activity study. The cost to benefit ratio was calculated on the basis of gross expenditure and net profit incurred in the trial field. The high contents of protein, fat and carbohydrate along with good anti-oxidant property and biological efficiency revealed the mushroom as a rich source of quality nutrients. The yield of 740.60 g/kg wheat straw withbenefit to cost ratio of 2.60 depicted economical viability of mushroom farming. The study concludes that, pink oyster mushroom farming can be explored for nutritional security in alleviating the malnutrition with economic benefits to the farmers in Uttarakhand.